Preparation and regeneration method of iron-aluminum-lanthanum-based composite fluorine removal agent
By adopting the preparation method of iron-aluminum-lanthanum-based composite fluorine removal agent, the efficiency and life problems of the existing fluorine removal agent when treating low-concentration fluorine-containing wastewater are solved, and efficient and stable fluorine removal effect and low regeneration cost are achieved.
Patent Information
- Application Number
- CN202510051534.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-15
AI Technical Summary
When the existing fluorine-depleting agents treat low-concentration fluorine-containing wastewater, there are problems such as small adsorption capacity, low treatment efficiency, long treatment time, and a decrease in exchange capacity after regeneration.
Using the preparation method of iron-aluminum lanthanum-based composite fluorine-removing agent, La(NO3)3·6H2O, Al(NO3)3 and Fe(NO3)3·9H2O were prepared in a molar ratio of 1:1:1, and excess triethanolamine and HNO3 solution were added, and the pH was adjusted to 3.0-4.0, and sufficient reaction and dehydration were carried out. Finally, the grey powder fluorine-removing agent was calcined to obtain, and its adsorption capacity was restored by pickling and regeneration method.
The adsorption capacity and processing efficiency of the fluorine-depleting agent are improved, the processing time is shortened, and the service life is extended through a simple pickling and regeneration method is reduced, thus reducing regeneration costs.
Smart Images

Figure CN119819250A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of defluorination agent preparation, in particular to a preparation and regeneration method of an iron-aluminum-lanthanum based composite defluorination agent. Background Art
[0002] Fluoride in urban sewage treatment plants generally comes from industrial wastewater and domestic sewage. The maximum allowable discharge concentration of fluoride in industrial wastewater is 10 mg / L, and fluoride in domestic sewage mainly comes from fluoride-containing products used in daily life, such as fluoride toothpaste, mouthwash and detergent. According to the "Surface Water Environmental Quality Standard" (GB3838-2002), the fluoride content of sewage treatment plant effluent shall not exceed 1.5 mg / L, while the "Sanitary Standard for Drinking Water" (GB5949-2006) stipulates that the fluoride content in drinking water shall not exceed 1.0 mg / L. Usually, the fluoride content in the designed influent water quality of urban sewage treatment plants is 10.0 mg / L, which belongs to low-concentration (1-10 mg / L) fluoride-containing wastewater, and the fluoride content in the designed effluent water quality is not higher than 1.0 mg / L.
[0003] At present, the commonly used defluorination processes in urban sewage treatment plants include precipitation, adsorption, ion exchange, coagulation and sedimentation, and biological treatment. In comparison, the adsorption method shows higher defluorination efficiency and stability when treating low-concentration fluoride-containing wastewater, and optimizing operating conditions (such as pH value, adsorption time, etc.) can extend the service life of the adsorbent and reduce operating costs. Commonly used defluorination adsorbents include activated alumina, clinoptilolite, activated magnesium oxide, hydroxyapatite, and zirconium oxide. These adsorbents can be used to treat wastewater with a fluoride concentration of 10 mg / L to below 1 mg / L, but there are also problems such as small filter material adsorption capacity, low treatment efficiency, long treatment time, and decreased exchange capacity after filter material regeneration. Therefore, there is an urgent need for a preparation and regeneration method of an iron-aluminum-lanthanum-based composite defluoridant to solve this problem. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing and regenerating an iron-aluminum-lanthanum based composite defluorinating agent, so as to solve the problem that the performance of the existing defluorinating agent needs to be improved.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing an iron-aluminum-lanthanum based composite defluorinating agent, comprising the following steps:
[0006] S1: La(NO 3 ) 3 6H 2 O、Al(NO 3 ) 3 and Fe(NO 3 ) 39H 2 O, fully stirred and dissolved in deionized water at room temperature, and the volume was adjusted to a clear mixed solution;
[0007] S2: Add excess triethanolamine to the mixed solution and add HNO 3 solution, adjusting the pH of the mixed solution to 3.0-4.0, continuing to stir at room temperature, and obtaining a precursor solution after sufficient reaction;
[0008] S3: The precursor liquid is continuously heated and stirred at 150°C for dehydration to obtain an organic brown fluffy precursor powder;
[0009] S4: Grind the precursor powder thoroughly and calcine to obtain a gray powdery iron-aluminum-lanthanum-based composite defluorinating agent.
[0010] Preferably, in the above step S2, the concentration of triethanolamine in the precursor solution is greater than three times the molar concentration of total metal ions.
[0011] Preferably, in the above step S2, after adjusting the pH, stirring is continued at room temperature for 1 hour, the mixed solution generates foam and expands, and the evaporation of nitrate ions provides an in-situ oxidation environment for the decomposition of hydroxyl groups on triethanolamine into carboxylic acids.
[0012] Preferably, in the above step S4, the precursor powder is calcined at 800° C. for 2 hours.
[0013] A regeneration method for an iron-aluminum-lanthanum-based composite defluorinating agent, wherein the iron-aluminum-lanthanum-based composite defluorinating agent prepared by the above preparation method adsorbs fluoride ions, and the specific regeneration process comprises: placing the iron-aluminum-lanthanum-based composite defluorinating agent adsorbing fluoride ions in HNO with a pH value of 3.0 to 4.0 3 The solution was stirred continuously at room temperature for 1 hour; it was first washed repeatedly with deionized water, then neutralized with NaOH solution, and after neutralization, it was washed repeatedly with deionized water and then dried.
[0014] Preferably, in the above regeneration process, the drying temperature is 150° C. and the product is ground into powder after drying.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. The preparation and regeneration method of the iron-aluminum-lanthanum-based composite defluorinating agent has a simple pyrolysis process flow, common reaction equipment, simple and safe operation, and a short production and regeneration cycle. The method uses TEA as a chelating agent to avoid precipitation. At the same time, a suitable pH is adjusted during the preparation process, and continuous heating and stirring are performed to generate foam and expansion. The nitrate ions evaporate, providing an in-situ oxidation environment for the decomposition of the hydroxyl groups on the TEA into carboxylic acids, which can increase the active sites on the surface of the defluorinating agent and further enhance the adsorption capacity of fluoride ions.
[0017] 2. The preparation and regeneration method of the iron-aluminum-lanthanum based composite defluoridating agent. The prepared iron-aluminum-lanthanum based composite defluoridating agent is suitable for adsorption and defluoridation under the condition of pH 6.0-7.0 in water body. It has stable defluoridation effect, large adsorption capacity and short reaction time. It is expected to be used in defluoridation work in urban sewage treatment plants. Most of the adsorption capacity can be restored by simple acid washing. It is simple to operate, has a long service life and a low regeneration cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic diagram of the process flow of the preparation method of the present invention. DETAILED DESCRIPTION
[0019] See also Figure 1 , a method for preparing an iron-aluminum-lanthanum based composite defluorinating agent, comprising the following steps:
[0020] S1: La(NO 3 ) 3 6H 2 O、Al(NO 3 ) 3 and Fe(NO 3 ) 3 9H 2 O, fully stirred and dissolved in deionized water at room temperature, and the volume was adjusted to a clear mixed solution;
[0021] S2: Add excess triethanolamine to the mixed solution and add HNO 3 solution, adjusting the pH of the mixed solution to 3.0-4.0, continuing to stir at room temperature, and obtaining a precursor solution after sufficient reaction;
[0022] In a preferred embodiment, the excess triethanolamine can be added such that the concentration of triethanolamine in the precursor solution is three times greater than the molar concentration of the total metal ions;
[0023] After adjusting the pH, the stirring time at room temperature can be further set to continue stirring for 1 hour, but it can also be adjusted according to experiments or experience. The mixed solution produces foam and expansion, and the evaporation of nitrate ions provides an in-situ oxidation environment for the decomposition of hydroxyl groups on triethanolamine into carboxylic acids;
[0024] S3: The precursor liquid is continuously heated and stirred at 150°C for dehydration to obtain an organic brown fluffy precursor powder;
[0025] S4: Grind the precursor powder thoroughly and calcine to obtain a gray powdery iron-aluminum-lanthanum-based composite defluorinating agent. For reference, the precursor powder can be calcined at 800° C. for 2 hours.
[0026] After the defluorination agent prepared above has adsorbed fluoride ions, it can be regenerated by the following simple steps: the iron-aluminum-lanthanum-based composite defluorination agent adsorbing fluoride ions is placed in HNO with a pH value of 3.0 to 4.0. 3 The mixture is stirred continuously at room temperature for 1 hour in the solution; first, it is repeatedly washed with deionized water, then neutralized with NaOH solution, and then washed repeatedly with deionized water after neutralization, and then dried. The drying temperature can be 150°C. After drying, it is preferably ground into powder for standby use.
[0027] Embodiment 1:
[0028] According to the molar ratio of iron ion, aluminum ion and lanthanum ion of 1:1:1, 43.3 g of La(NO 3 ) 3 6H 2 O, 21.3 g of Al(NO 3 ) 3 and 24.2 g Fe(NO 3 ) 3 9H 2 O, fully stirred and dissolved in deionized water at room temperature, and the volume was adjusted to 1 liter of clear mixed solution, and the concentration of iron, aluminum and lanthanum ions in the mixed solution was 0.1 mol / L;
[0029] Excess triethanolamine (TEA) was added to the mixed solution, followed by the addition of HNO 3 solution, adjusting the pH of the mixed solution to 3.0-4.0, and continuing stirring at room temperature for 1 hour to obtain a precursor solution after sufficient reaction;
[0030] The precursor liquid is continuously heated and stirred at 150°C for dehydration, and a large amount of organic brown fluffy powder, i.e., precursor powder, is left after complete dehydration;
[0031] The precursor powder is fully ground and then calcined at 800°C for 2 hours. The gray powder obtained after calcination is the iron-aluminum-lanthanum based composite defluorination adsorption material.
[0032] The iron-aluminum-lanthanum-based composite defluorination adsorption material prepared in this embodiment was used to measure the effect of adsorption time on its defluorination efficiency. The specific operation and measurement results are as follows:
[0033] Fluoride solutions with initial concentrations of 3 mg / L, 5 mg / L and 10 mg / L were prepared using sodium fluoride stock solution and deionized water, and the solution pH was 7.0±0.2. Four 100 mL portions of fluoride solution of each concentration were taken, and 0.2 g of an iron-aluminum-lanthanum-based composite defluoridant was added to each portion. Under room temperature, four portions of fluoride solutions of each concentration were magnetically stirred for 15 min, 30 min, 45 min and 60 min, respectively, and the supernatant was taken to determine the corresponding defluoridation rate. The results are shown in Table 1 below:
[0034] Table 1
[0035] 15min 30min 45min 60min 3mg / L 94.1% 90.0% 98.6% 99.2% 5mg / L 85.4% 80.1% 99.1% 99.4% 10mg / L 99.9% 96.0% 98.4% 97.8%
[0036] It can be seen that the fluoride ion concentration in the treated water is lower than 1 mg / L. The general trend is that the fluoride removal rate decreases at first, and then as time goes on, the fluoride removal rate steadily increases to reach adsorption saturation or equilibrium. In the initial stage (0-15min), the high specific surface area and porous structure of the adsorbent material provide more adsorption points; in the middle stage (15-30min), after the adsorbed fluoride ions diffuse into the pores of the adsorbent, part of the adsorbed fluoride is released due to the repulsion between the fluoride ions and the reduction of the specific surface area; in the late reaction, the adsorption equilibrium or saturation is basically reached after 60min.
[0037] Embodiment 2:
[0038] The iron-aluminum-lanthanum-based composite defluorination adsorption material prepared in Example 1 was used to measure the effect of the amount of defluorination agent added on its defluorination efficiency. The specific operation and measurement results are as follows:
[0039] Fluoride solutions with initial concentrations of 3 mg / L, 5 mg / L and 10 mg / L were prepared using sodium fluoride stock solution and deionized water, with a pH of 7.0 ± 0.2. Four 100 mL portions of fluoride solution of each concentration were taken, and 0.05, 0.1, 0.2 and 0.3 g of iron-aluminum-lanthanum composite defluoridation agent were added respectively. After magnetic stirring for 45 minutes at room temperature, the supernatant was taken to determine the corresponding defluoridation rate. The results are shown in Table 2 below:
[0040] Table 2
[0041] 0.05g 0.1g 0.2g 0.3g 3mg / L 68.5% 92.1% 98.6% 98.8% 5mg / L 42.7% 46.8% 99.1% 99.1% 10mg / L 73.8% 96.7% 98.4% 99.1%
[0042] As the amount of defluoridation agent added increases, the defluoridation rate is higher. It can be seen that when the amount of defluoridation agent added is 0.2g / 100ml, the pH of the fluoride solution is 7.0, and the reaction time is 45 minutes, the fluoride concentration in the water treated with the three initial concentrations of fluoride solution is lower than 1mg / L.
[0043] Embodiment 3:
[0044] The iron-aluminum-lanthanum-based composite defluorination adsorption material prepared in Example 1 was used to measure the effect of the pH of the fluoride solution to be treated on the defluorination efficiency. The specific operation and measurement results are as follows:
[0045] A fluoride solution with an initial concentration of 3 mg / L was prepared using sodium fluoride stock solution and deionized water. NaOH and HNO 3The solution was adjusted to a pH value of 3 mg / L fluoride solution, and 100 mL of each fluoride solution with pH values of 4, 6, 7, 8, and 10 was prepared. 0.2 g of an iron-aluminum-lanthanum composite defluoridant was added. After magnetic stirring for 45 minutes at room temperature, the supernatant was taken to determine the corresponding defluoridation rate. The results are shown in Table 3 below:
[0046] Table 3
[0047] 4 6 7 8 10 3mg / L 95.2% 97.1% 98.6% 90.3% 79.9%
[0048] It can be seen that when the pH of the fluoride solution is between 6.0 and 7.0, the fluoride removal rate is higher.
[0049] Embodiment 4:
[0050] Twelve groups of iron-aluminum-lanthanum-based composite defluorination adsorbent materials that adsorbed fluoride ions in Example 2 were regenerated and the remaining adsorption capacity was measured. The specific operation and measurement results are as follows:
[0051] The 12 groups of Fe-Al-L-based composite defluoridants with fluoride ions adsorbed were placed in HNO 3 The solution was stirred continuously at room temperature for 1 hour; it was first washed repeatedly with deionized water, then neutralized with NaOH solution, and after neutralization, it was washed repeatedly with deionized water, and then dried at 150°C and crushed to complete regeneration.
[0052] Fluoride solutions with initial concentrations of 3 mg / L, 5 mg / L and 10 mg / L were prepared using sodium fluoride stock solution and deionized water, and the solution pH was 7.0±0.2. Four 100 mL portions of fluoride solution of each concentration were taken, and the above 12 groups of regenerated iron-aluminum-lanthanum-based composite defluoridants were added to the corresponding fluoride solutions according to the original experimental concentrations. After magnetic stirring for 45 minutes at room temperature, the supernatant was taken to determine the corresponding defluoridation rate. The results are shown in Table 4 below:
[0053] Table 4
[0054] 0.05g 0.1g 0.2g 0.3g 3mg / L 59.3% 78.29% 83.10% 86.23% 5mg / L 41.80% 42.50% 85.33% 85.12% 10mg / L 68.31% 82.20% 83.64% 89.38%
[0055] The residual adsorption capacity after regeneration is represented by the ratio of the fluorine removal rate after regeneration in Table 4 to the fluorine removal rate before regeneration in the table. The lowest among the 12 groups of data is 84.28% calculated by the experimental group in which 0.2g of defluorine agent was added to the 3mg / L solution. The average residual adsorption capacity of the 12 groups reached more than 88%, which shows that the iron-aluminum-lanthanum based composite defluorine agent prepared by the method of the present invention has excellent regeneration performance.
[0056] The above are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.
[0057] The matters not described in detail in the present invention are all known technologies to those skilled in the art.
Claims
1. A method for preparing an iron-aluminum-lanthanum based composite defluorinating agent, characterized in that: The following steps are involved: S1: La(NO3)3·6H2O, Al(NO3)3 and Fe(NO3)3·9H2O were weighed in a molar ratio of 1:1:1 among iron ions, aluminum ions and lanthanum ions, and dissolved in deionized water at room temperature with sufficient stirring, and a clear mixed solution was prepared by constant volume; S2: adding an excess of triethanolamine to the mixed solution, dropping HNO3 solution, adjusting the pH of the mixed solution to 3.0-4.0, continuing to stir at room temperature, and obtaining a precursor solution after sufficient reaction; S3: The precursor liquid is continuously heated and stirred at 150°C for dehydration to obtain an organic brown fluffy precursor powder; S4: Grind the precursor powder thoroughly and calcine it to obtain a gray powdery iron-aluminum-lanthanum-based composite defluorinating agent.
2. The method for preparing an iron-aluminum-lanthanum based composite defluorinating agent according to claim 1, characterized in that: In step S2, the concentration of triethanolamine in the precursor solution is greater than three times the molar concentration of total metal ions.
3. The method for preparing an iron-aluminum-lanthanum based composite defluorinating agent according to claim 1, characterized in that: In step S2, after adjusting the pH, stirring is continued at room temperature for 1 hour, the mixed solution generates foam and expands, and the evaporation of nitrate ions provides an in-situ oxidation environment for the decomposition of hydroxyl groups on triethanolamine into carboxylic acids.
4. The method for preparing an iron-aluminum-lanthanum based composite defluorinating agent according to claim 1, characterized in that: In the step S4, the precursor powder is calcined at 800° C. for 2 hours.
5. A method for regenerating an iron-aluminum-lanthanum-based composite defluorinating agent, characterized in that: The iron-aluminum-lanthanum-based composite defluoridant prepared by the preparation method described in any one of claims 1 to 4, after adsorbing fluoride ions, the specific contents of regeneration include: placing the iron-aluminum-lanthanum-based composite defluoridant adsorbing fluoride ions in a HNO3 solution with a pH value of 3.0 to 4.0, and continuously stirring at room temperature for 1 hour; first repeatedly washing with deionized water, and then neutralizing with NaOH solution, and after neutralization, continue to use deionized water to repeatedly wash and then dry.
6. The regeneration method of an iron-aluminum-lanthanum based composite defluorinating agent according to claim 5, characterized in that: The drying temperature is 150° C. and the mixture is ground into powder after drying.
Citation Information
Cited By
Photovoltaic wastewater treatment agent and preparation method thereof
CN120885187A
Efficient liquid fluorine removal agent based on terpolymer
CN121085393A
A highly efficient liquid fluorine removal agent based on a terpolymer
CN121085393B
Defluorination method of lithium sulfate solution, composite defluorination agent and preparation method of composite defluorination agent
CN121225624A
Preparation method and application of fluorine removal agent
CN121244185A